Cervical Dysplasia and Treatments Barrier in Jail: A Study in Marseille's Detention Center?Les Baumettes, France - Claire Delage de Luget; Camille Jauffret; Cindy Faust; Sophie Knight; Christophe Bartoli; Emilie Ricard (Mary Ann Liebert, 2022)
Introduction: The main objective was to estimate the prevalence of cervical dysplasia among incarcerated women. The secondary objective was to identify obstacles to the possible management of a cervical dysplasia in detention by assessing their knowledge of screening for cervical cancer (CC), the existence of vaccination, and the management of precancerous lesions. Materials and Methods: The first part of the study was descriptive and retrospective, studying pap-smear results in women's correctional facility at the Baumettes prison center (PC) in Marseille, France. The second part of the study was qualitative and prospective and took place at the Baumettes PC. Voluntary and French-speaking inmates aged 25?65 years answered an short-form 12 quality-of-life questionnaire and a more targeted questionnaire on CC screening and cervical dysplasia treatments. Results: In total, 201 pap-smear tests were assessed, 135 were normal (66.8%) and 33 unsatisfactory (16.3%). There were 33 abnormal pap-smear tests (16%). The patients were 38.9 years (?9.5 years), had 4.05 pregnancies (?2.7), and 2.29 children (?1.85). Seventy-five percent were smokers. Psychiatric disorders were found in 52.2% inmates. In the second part of the study, among the 35 inmates questioned, the SF-12 questionnaire's analysis shows that the physical health component score was on average 43.6 and the mental health component score (MCS) was 36.5. Analysis demonstrated that the uncertainty of the exact day of hospitalization is an obstacle to treatment for 15 patients presenting significantly a lower MCS score (p?=?0.047). Conclusion: Prevalence of pathological pap-smear tests is higher within a prison population, screening is accepted and the inmates are receptive to information about CC prevention, delivered during individual interviews. Mental health's management and care system's reorganization in detention are essentials factors for care acceptance.